NOTARISASI PROGRAM IN THE DISTRICT COTTAGE BOARDING BOGOR - Roestamy, Martin (QARDHUL HASAN: MEDIA PENGABDIAN KEPADA MASYARAKAT, 2016)
This devotion is motivated by the fact that some regional boarding school in Bogor districthas not had a notary deed of establishment boarding school. Given the importance of thenotarial deed for the boarding school community service program is designed in the form ofnotarisasi boarding school. Advantages of the boarding school has a notary deed that is oneof the beneficiaries as requirements boarding school dormitory this matter by the Ministry ofReligious Affairs Directorate General of Islamic Education. Interest notarisasi boardingservice activities are: 1) notarisasi establishment of boarding schools, 2) legal aid, 3) for thevalidation of pesantren and 4) assist in the process of getting assistance from thegovernment Dansos West Java Province. Results from community service program that hasthe deed boarding school boarding school, receive legal aid, assisted in the process of gettingassistance from the government Dansos West Java Province. Boarding schools that receivecommunity service that is notarisasi boarding school located in the district of Bogor includeIbnul Hidayah Boarding School, Pondok Pesantren Al-Muklisin, Pondok Pesantren Al-Fudhaliyah, Pondok Pesantren Ibtidaul Hudda, as well as Miftahul Huda Islamic boardingschool.